1978
DOI: 10.1128/iai.19.1.58-65.1978
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the immunoprotective antigen of ribosomal preparations from Haemophilus influenzae

Abstract: This investigation was designed to characterize the immunoprotective antigen of ribosomal preparations from Haemophilus influenzae. The ribosomes that elicited 80 to 90% protection contained 25% protein and 75% ribonucleic acid but did not contain any detectable hexoses. The immunodiffusion and hemagglutination inhibition tests also failed to demonstrate that the capsular material (polyribose phosphate) was in ribosomal preparations. Treatment of ribosomes with ribonuclease degraded 78% ribonucleic acid but di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The ribosomal suspension was standardized on the basis of protein content by the method of Lowry et al (8). The chemical composition of the ribosomes was similar to that previously described (10,13). The relative amounts of ribonucleic acid, protein, and hexose were 65, 35, and 0%, respectively.…”
Section: Methodssupporting
confidence: 68%
See 1 more Smart Citation
“…The ribosomal suspension was standardized on the basis of protein content by the method of Lowry et al (8). The chemical composition of the ribosomes was similar to that previously described (10,13). The relative amounts of ribonucleic acid, protein, and hexose were 65, 35, and 0%, respectively.…”
Section: Methodssupporting
confidence: 68%
“…It has been reported that ribosomes from Haemophilus influenzae induce active immunity against a lethal H. influenzae type b infection in experimental animals; ribosomes were free from detectable capsule and cell wall components, and protein was the immunogenic moiety in these ribosomes (10,13).…”
mentioning
confidence: 99%
“…Although thevalueofribosomal vaccines is now established, doubt remains as to their mechanism ofaction and as to the exact nature of the immunogenic principle responsible for their activity. Many authors have demonstrated the presence of small amounts of surface antigens in ribosomal preparations from Streptococcus pneumoniae (3,4), Pasteurella multocida ( 5 ) , Vibrio cholerae (1 7), Salmonella typhimurium (7,18,23) and Hemophilus influenzae (32). In a previous study, we have shown that polysaccharide antigens were also strongly bound to the r-RNA isolated from various strains (24).…”
mentioning
confidence: 92%
“…Bacteria used in bactericidal and opsonophagocytic studies and for adsorption were grown in Mueller-Hinton broth supplemented with 10 ,ug each of hemin and NAD (Sigma Chemical Co., St. Louis, Mo.) per ml at 37°C; incubation was for about 18 30 60 90 120 TIME (MINUTES) FIG. 1.…”
mentioning
confidence: 99%
“…(2,3,10,17,19,28,30). It is reasonable to believe that these same kinds of antibody may contribute to immunity to NT H. influenzae.INFECT.…”
mentioning
confidence: 99%